Adverse Events in Young and Preterm Infants Receiving Topical Timolol for Infantile Hemangioma. Issue 4 (31st May 2016) - Frommelt, Peter; Juern, Anna; Siegel, Dawn; Holland, Kristen; Seefeldt, Marcia; Yu, JiaDe; Uhing, Michael; Wade, Kelly; Drolet, Beth
Abstract: Background: The success of oral propranolol for treatment of infantile hemangiomas (IHs) has led practitioners to use topical β‐blockers. In preterm infants, clinicians frequently turn to topical timolol, with the presumption that topical application will result in less systemic absorption. We used Holter monitoring to assess for drug‐induced bradycardia in high‐risk infants. Methods: We retrospectively reviewed the charts of 22 at‐risk infants who received a Holter monitor to assess for association between timolol administration and development of significant bradycardia. Results: Four infants had episodic bradycardia detected by Holter monitoring. Two of these infants were full term; weighed more than 3, 000 g; and had rare, brief, asymptomatic episodes unrelated to the timing of the timolol application. The other two infants had symptomatic bradycardia while on timolol and were the only two babies that weighed less than 2, 500 g at initiation of therapy. Both were young (postmenstrual age [PMA] 34 and 37 wks) at initiation and had a timolol dose above the average exposure for the cohort. Conclusion: In this cohort of at‐risk infants, topical timolol appeared to provide safe treatment for IHs in full‐term infants receiving a dose of less than 0.2 mg/kg/day, but infants with a PMA of less than 44 weeks and weight at treatment initiation of less than 2, 500 g may be at risk of adverse events, including bradycardia, hypotension, apnea, and hypothermia. We recommend close monitoring of temperature, blood pressure, and heart rate in premature and low‐birthweight infants with IHs at initiation of and during therapy with topical timolol.